2010
DOI: 10.1111/j.1551-2916.2009.03547.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Blue Emission from Transparent Oxyfluoride Glass–Ceramics Containing Pr3+:BaF2Nanocrystals

Abstract: Transparent glass–ceramics containing Pr3+:BaF2 nanocrystals in the chemical composition of SiO2–BaF2–K2CO3–La2O3–Sb2O3 oxyfluoride glass systems have been prepared from melt quenching and with a subsequent heat‐treatment method. The luminescence and structural properties of these materials have been evaluated and the results are reported. Rietveld analysis of X‐ray diffraction patterns and investigation of transmission electron microscopy confirmed the presence of BaF2 nanocrystals dispersed in the heat‐treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 31 publications
(40 reference statements)
2
31
1
Order By: Relevance
“…2. As, BaF 2 has a lower refractive index compared to the precursor glass, the refractive indices of glass-ceramic samples tend to decrease with the increase in the degree of ceramization [25]. Table 1 also shows that there is a decrease in the density of samples upon ceramization.…”
Section: Physical and Optical Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…2. As, BaF 2 has a lower refractive index compared to the precursor glass, the refractive indices of glass-ceramic samples tend to decrease with the increase in the degree of ceramization [25]. Table 1 also shows that there is a decrease in the density of samples upon ceramization.…”
Section: Physical and Optical Propertiesmentioning
confidence: 89%
“…Due to the low phonon energy sites of alkaline-earth fluoride nano-crystallites (300-400 cm −1 ), they exhibit efficient fluorescent properties with an enhanced emission efficiency and longer lifetimes because of the reduced non-radiative relaxations and possess high solubility of both sensitizer and activator rare earth ions. Recently, the photoluminescence properties of Pr 3+ doped SiO 2 -BaF 2 -K 2 CO 3 -La 2 O 3 -Sb 2 O 3 based transparent oxyfluoride glass and glass-ceramics containing BaF 2 nano-crystals have been studied by our group [25]. In this glass system, SiO 2 takes the role of glass network former while BaF 2 , K 2 O, and La 2 O 3 being network modifies and Sb 2 O 3 acts as refining agent.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, researchers considered that rare earth activators are almost completely extracted by forming fluoride nanocrystals, i.e., distribution coefficients of rare earth ions between formed nanocrystals and their glass matrixes were very high. Moreover, R/M ratio in these fluorite-type nanophases in regard to the same R/M ratio in the initial glass (so-called segregation coefficient k) very frequently exceeds 1 (like in [41]): k is about 1.5-2.0 in [55,142,131,132]. However, de Pablos-Martin et al [25] found that for alumosilicate glasses thulium was present in both glass matrix and nanocrystalline LaF 3 .…”
Section: Phase and Chemical Composition Of The Nanocrystalsmentioning
confidence: 91%
“…1200 o C for germinate or borate glasses. Preparation of glass ceramics from of aluminosilicate [35-A c c e p t e d M a n u s c r i p t 6 40], silicate [41], silicoborate [42][43][44], lead-silicate [45][46][47], quartz [48][49][50][51][52][53], lead-germanate [54][55][56], tellurate-germanate [57], zinc-tellurate [58], lithiumborate, potassium-borate, barium-borate [59,60], tungsten-lead-phosphate [61] and others glasses with high metal fluoride content is thoroughly described in the literature (see Table 1). …”
Section: Types Of Glass Ceramicsmentioning
confidence: 99%
“…In addition, the oxyfluoride matrixes combine in itself the properties of both crystal and glass that allows: extruding them, creating of large size samples, pulling the fiber, as well as carrying of ion exchange processes to produce waveguide structures. Oxyfluoride matrixes are well known for their relatively low effective phonon energy (approximately 400 cm -1 [5]) due to fluorides and the optimal size of ionic radius for doping RE phosphors that provides minimization of non-radiative losses and, as a result, more efficient UCL [6][7][8] Among other RE elements europium is considered as one of the most perspective elements for phosphors applications due to its high quantum efficiency in the orange-red range of the spectrum and, as a result, it can be used as a red phosphor for television displays, fluorescing lamps, etc. [9].…”
mentioning
confidence: 99%